A Knowledge-Based Economy Perspective of Technology Transfer - Ellitan, Lena (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2007)
This contribution proposes a revised framework for understanding and analyzing the process of technology transfer in the perspective of the knowledge-based economy (KBE). The underlying hypothesis is that the context of the knowledge-based economy introduces a major shift in the way technology transfer is conceived. The traditional model of technology transfer was based on the vision of technology moving from one well-defined economic unit to another well-defined unit. We suggest that in the new perspective technology transfer is essentially considered as a specific knowledge-transfer process that depends on the ways firms and other institutions manage knowledge, in particular the co-evolution of their absorptive capabilities and their knowledge-transmission strategies. Keywords: Technology transfer; Management of knowledge; Diffusion of technology